Detection and quantification of residual disease in chronic myelogenous leukemia - Hochhaus, Andreas; Weißer, Andreas; La Rosée, Paul; Emig, Michael; Müller, Martin Christian; Saußele, Susanne; Reiter, Andreas; Kuhn, Christian; Berger, Ute; Hehlmann, Rüdiger; Cross, Nicholas C. P. (Leukemia, 2000)
The degree of tumor load reduction after therapy is an important prognostic factor for patients with CML. Conventional metaphase analysis has been considered to be the ‘gold standard’ for evaluating patient response to treatment but this technique normally requires bone marrow aspiration and is therefore invasive. The frequency of cytogenetic analyses can be considerably reduced if patients are also monitored by molecular methods, which can be performed on peripheral blood specimens. Of the various techniques available, most attention has been paid to RT-PCR for BCR-ABL mRNA since this is by far the most sensitive. Simple, non-quantitative RT-PCR analysis gives only limited information on patients after treatment. Quantitative RT-PCR assays have been developed to monitor the kinetics of residual BCR-ABL transcripts over time. Variables in the quantitative PCR assay may be controlled for by quantification of transcripts of a normal gene (eg ABL or glucose-6-phosphate dehydrogenase, G6PD) as an internal standard. After allogeneic stem cell transplantation, most patients become RT-PCR negative, often after a period of low level positivity that may persist for several months. Those patients destined to relapse are characterized by the reappearance and/or rising levels of BCR-ABL transcripts. In contrast, for patients treated with interferon-α (IFN) residual disease is rarely, if ever, eliminated. The actual level of minimal residual disease in complete cytogenetic responders to IFN correlates with the probability of relapse. New quantitative real time procedures promise to simplify the protocols that are currently in use, but standardization and the introduction of rigorous, internationally accepted controls are required to enable RT-PCR to become a robust and routine basis for therapeutic decisions.
Gesehen am 13.04.2022